Land Policy for SEZ - J. S. Bali (Journal of Soil and Water Conservation, 2022)
Land is finite while its needs are infinite. We have to ration land. Land budgeting is a tool to aid in land rationing. It has been attempted in this principle. Two sacrosanct land pools have been proposed which should not be touched for industrial, housing or any other non-agricultural use, The first is the National Food Security Land, NFSL, of 193.26 mha which takes care of food, and fodder for the people and their animals. The second is the National Eco-Security land, NESL, of 69.67 mha of the forestland. The third pool for Housing, Industry and infrastructure Land which comprises 42.30 mha is the only one which should normally be available for the industry and other non agricultural uses. But this contains barren and inaccessible lands. If both food and environmental security are our vital needs, we have got to pay a price for the reclamation of other difficult lands and make them available for housing and industry etc. More than a dozen other land policy principles for SEZ have also been stated and their rationale explained. Industry is necessary for modern living. Food and air are essential for living itself.